Histo-Morphometrical Study on the Pancreas of Turkey - Suri, Shalini; Sasan, Jasvinder S.; Khan, Asma (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was conducted on the pancreas of 06 turkey birds. The pancreas of turkey is located between the descending and ascending parts of the duodenum with total length of 9.82 ± 0.28 cm, width of 2.17 ± 0.10 cm and thickness of 1.12 ± 0.08 cm. Histologically, the parenchyma of pancreas consisted of both exocrine and endocrine portion. The exocrine part composed of serous tubulo-acinar glands. Acinar cells were pyramidal to tall columnar in shape with round, basally situated nucleus with a prominent nucleolus and apically located acidophilic zymogen granules. The average longer diameter was 50.73 ± 5.59 µ whereas the smaller diameter was 35.08 ± 3.80 µ. The average height of acinar cell was 15.63 ± 1.59 µ with average nuclear diameter of 6.87 ± 0.35 µ. The ducts located within the lobules were small and lined by simple cuboidal to low columnar epithelium. The endocrine part consisted of islets of Langerhans. The average longer diameter was 49.26 ± 1.41 µ whereas the smaller diameter was 43.61 ± 1.23 µ.